2017
DOI: 10.1371/journal.pntd.0005867
|View full text |Cite
|
Sign up to set email alerts
|

Increased hepatotoxicity among HIV-infected adults co-infected with Schistosoma mansoni in Tanzania: A cross-sectional study

Abstract: IntroductionLittle is known about hepatotoxicity in patients with schistosome and HIV co-infections. Several studies have reported increased liver enzymes and bilirubin levels associated with schistosome infection. We investigated whether HIV-infected adults on antiretroviral therapy who had S. mansoni co-infection had a higher prevalence of hepatotoxicity than those without.Methodology/Principal findingsWe determined the presence and grade of hepatotoxicity among 305 HIV-infected outpatients who had been on m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…One study reported that S . mansoni -HIV coinfection was associated with elevated liver transaminases after controlling for other known causes of transaminitis (HBV, HCV, alcohol, medications) in patients on ART [ 88 ]. This suggests that S .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study reported that S . mansoni -HIV coinfection was associated with elevated liver transaminases after controlling for other known causes of transaminitis (HBV, HCV, alcohol, medications) in patients on ART [ 88 ]. This suggests that S .…”
Section: Resultsmentioning
confidence: 99%
“…Schistosomes and HIV virulence. One study reported that S. mansoni-HIV coinfection was associated with elevated liver transaminases after controlling for other known causes of transaminitis (HBV, HCV, alcohol, medications) in patients on ART [88]. This suggests that S. mansoni infection could potentiate direct hepatotoxicity of HIV on hepatocytes [89].…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Among Western populations, the prevalence of liver fibrosis among HIV-infected patients was similar to the findings of our study and other studies in SSA, with estimates of 16%–29% [ 20 ]. Antiretroviral therapy has been demonstrated to reduce risk of liver fibrosis via adequate viral suppression [ 8 , 30 ]. In resource-limited settings, rollout of HIV care programs started in urban settings long before their initiation within hard-to-reach areas [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Figure 2 details the study selection procedure. Of the 364 abstracts identified ( Figure 2 ), 29 focused on HIV and S. haematobium and/or S. mansoni , and 26 were included in the summary ( Brodish and Singh, 2016 ; Downs et al, 2017b ; Colombe et al, 2018 ; Noormahomed et al, 2014 ; Stete et al, 2018 ; Sanyaolu et al, 2016 ; Costiniuk et al, 2012 ; Sadlier et al, 2013 ; Efraim et al, 2013 ; Lar et al, 2016 ; Tegegne et al, 2017 ; Marti et al, 2017 ; Olusegun et al, 2011 ; Kallestrup et al, 2005 ; Mazigo et al, 2014 ; Kleppa et al, 2015 ; Mwanakasale et al, 2003 ; Ndhlovu et al, 2007 ; Kjetland et al, 2006 ; Downs et al, 2012 ; Woodburn et al, 2009 ; Sanya et al, 2015 ; Ssetaala et al, 2015 ; Downs et al, 2011 ; Wall et al, 2018 ) ( Table 1 ): nine reported the association of HIV and schistosomiasis; 11 reported the prevalence of schistosomiasis among people with HIV; and six reported the prevalence of HIV among people with schistosomiasis (one of these papers also reported an odds ratio for the association between schistosomiasis and HIV). One ecological analysis, one mathematical modelling paper and one summary of HIV and schistosomiasis among children were also evaluated.…”
Section: Methodsmentioning
confidence: 99%